2015
DOI: 10.1155/2015/639587
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroidectomy Is Associated with Reduced Mortality in Hemodialysis Patients with Secondary Hyperparathyroidism

Abstract: Secondary hyperparathyroidism increases morbidity and mortality in hemodialysis patients. The Kidney Disease Outcomes Quality Initiative Guidelines recommend parathyroidectomy for patients with chronic kidney disease and parathyroid hormone concentrations exceeding 800 pg/mL; however, this concentration represents an arbitrary cut-off value. The present study was conducted to identify factors influencing mortality in hemodialysis patients with parathyroid hormone concentrations exceeding 800 pg/mL and to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 14 publications
2
21
0
1
Order By: Relevance
“…It demonstrated that 1-year mortality rate was significantly higher among patients without a history of PTX comparing with those with a history of PTX [12]. Even if shortterm mortality, mostly in immediate postoperative period, was increased, decreased long-term mortality was the main result in other studies [8,13]. Trombetti et al [14] suggest that the survival advantage of patients after PTX is because healthier patients with fewer comorbidities are selected for the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It demonstrated that 1-year mortality rate was significantly higher among patients without a history of PTX comparing with those with a history of PTX [12]. Even if shortterm mortality, mostly in immediate postoperative period, was increased, decreased long-term mortality was the main result in other studies [8,13]. Trombetti et al [14] suggest that the survival advantage of patients after PTX is because healthier patients with fewer comorbidities are selected for the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Of them, 37 studies were retrieved for detailed evaluation, and finally 24 studies were excluded due to absence of information on the outcomes of interest (19 articles) or provision of data only in abstract form (5 articles). Finally, 13 studies [19][20][21][22][23][24][25][26][27][28][29][30][31] fulfilled the eligibility criteria ( Figure 1), with 10052 PTx-treated patients and 12001 medically-treated patients (totally 22053 patients). The 13 studies were all cohort studies with sample sizes from 20 to 4558 patients, and reported prevalence rates of diabetes from 0% to 44.3%.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
“…Most studies adjusted a wide range of potential confounders to investigate the association between PTx and all-cause mortality, including age, sex, body mass index (BMI), diabetes, duration of dialysis, and dialysis modality. Twelve studies presented data with all-cause mortality [19][20][21][22][23][24][25][26][27][28][29]31 and six studies with cardiovascular mortality. 19,20,23,26,28,30 Table 1 lists the key characteristics of the 13 studies.…”
Section: Selection and Characteristics Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…When quality of life becomes much compromised, the deformities are important and the bone pain intractable, surgery becomes the best option. In general, total parathyroidectomy with a forearm implant has been an excellent therapeutic option, reversing these negative factors 10 . The objective of this study was to evaluate the benefit of parathyroidectomy (PTx) on quality of life, body weight, biochemical and metabolic parameters in dialytic chronic renal disease.…”
Section: Introductionmentioning
confidence: 99%